Household Drug Stockpiling and Panic Buying of Drugs During the COVID-19 Pandemic: A Study From Jordan - Al Zoubi, Sura; Gharaibeh, Lobna; Jaber, Hatim M.; Al-Zoubi, Zaha (Frontiers in Pharmacology, 2021)
The coronavirus disease that emerged in 2019 (COVID-19) has affected health, societies and economies. Policies that have been imposed by different countries to slow the spread of the disease, including national lockdowns, curfews, border closures and enforcement of social distancing measures have disturbed the drug supply chain and resulted in drug shortages. Uncertainty concerning the pandemic has also led to the panic buying of drugs and the stockpiling of drugs in households, which has amplified the problem. In this cross-sectional study, a self-developed questionnaire was distributed online in order to a) assess the practice of household drug stockpiling prior to the national lockdown in Jordan, b) investigate the factors affecting it and c) measure peoples’ knowledge about the consequences of this behaviour. Results from this study show that drug purchasing was reported by 44.3% of the participants and was most common among participants from non-medical backgrounds (336, 75.7%) or those who have chronic diseases (261, 58.8%) and taking chronic supplements (282, 63.5%) regardless of their age, gender, living area or the possession of health insurance. Analgesics and antipyretics were the most frequently purchased drugs (225, 70.5%) and anticipation of their need was the most common reason for purchasing drugs (231, 52.0%). Buyers were also less aware, when compared to non-buyers, that panic buying and drug stockpiling may lead to drug shortages (204, 45.9% vs 325, 58.1%) and that this behaviour can pose a health hazard, especially to children (221, 47.5% vs 342, 61.2%). Our study shows that panic buying of drugs and household drug stockpiling were common in Jordan during the COVID-19 pandemic and this was related to participants’ medical knowledge and educational backgrounds. Therefore, educating the general population regarding rational drug use is urgently needed. This is also a compelling case for the development of national guidelines for drug management that target the general population and healthcare personnel, especially pharmacists, to avoid drug shortages during crises.